Effect of Mouthwash (THYMOL AND LISTRAEM) on Oral Microbiota (Bacteria) - Flafel , Fatima Moftah; Ali, Hasan Mohamed (The annual Scientific Conference for Under and Postgraduate Students at the University., 2023)
Oral health is the appropriate path leading to the general safety of the human body. Therefore, establishing and maintaining oral health is important, as large numbers and different types of microorganisms that are beneficial and harmful to oral health live inside the human mouth since childhood, and the presence of these organisms, whether they are bacteria or fungi. It is not considered dangerous or harmful because they exist naturally and in balance, as they contribute to a healthy balance in the mouth. Using types of mouthwash that contain chemicals are effective in reducing the number of bacteria or killing them. Using mouthwash has become a daily matter related to hygiene. Personality of the individual, as it is used as an antiseptic and antimicrobial agent. Mouthwash is not only used at home, but is also used before and after oral surgeries such as tooth extraction or orthodontic operations under the supervision of a dentist. The aim of this research is to measure the effect of mouthwash on the population of natural oral bacteria. Two types of mouthwash (LISTREAM & THYMOL) were used, and saliva was used as a miniature model of the oral microbial community. The bacteria were isolated in pure cultures using a serial dilution method. Dilution, and the study was applied to 17 samples of female students from the Zliten College of Education, and the research came out with the following results: In the samples treated with Control water, the number of bacterial colonies could not be counted, while the effect of Listream mouthwash was stronger than Thymol by 76%, and we cannot say that Thymol It has no effect on the number of bacteria when compared with the results of Control. Conclusion of the research Mouthwash contains chemicals that work to reduce the number of natural bacteria living inside the oral cavity. Therefore, the mouthwash must be used in a balanced way so as not to cause an adverse effect.